GEOSYSTEMS MAPPING OF RIFT REGION OF THE SIBERIA - M. A. Kotovschcikova; V. N. Nogovitsyn; T. I. Konovalova (InterCarto. InterGIS, 2014)
The methodic of geosystems mapping of the rift region of the Siberia on the base of learning of V.B. Sochava and the results are described. An example of geosystems map of this methodic is shown.